A Quartet of Diplomatic Memoirs - Kenneth Weisbrode (European Journal of Life Writing)
The diplomatic memoir is a peculiar subgenre of life writing. Diplomats are trained to be circumspect and occasionally economical with the truth, yet their writing is meant, in principle, to be candid, honest, and thorough. Diplomatic memoirists continue serving their profession but invert diplomatic practice, and the subgenre, in enacting a private, professional language in public with their memoirs. This essay examines the memoirs of four diplomats – an American, Englishman, Pakistani, and Turk – alongside their lives, families, style, and literary as well as historical significance.